Analysis of Academic Information System Website Service Quality at PGRI Palembang University Using The Webqual 4.0 Method - Irpan Kurniyado (Institute of Information Technology and Social Science (IITSS), 2024)
The rapid development of information technology has made the website an integral component of educational institutions, particularly in providing services to the academic community, including lecturers, students, and educational staff. The quality of internet-based academic information system (AIS) services must be evaluated to ascertain the level of user satisfaction. Currently, the PGRI AIS is prioritized in academic information processes, especially for students; therefore, an analysis of service quality—specifically user satisfaction—is essential for its improvement. This research measured the quality of the AIS website at PGRI Palembang University using the Webqual 4.0 method. Data were collected by distributing questionnaires via Google Form. WebQual is an instrument designed to assess a website's quality from the perspective of the end-user. Multiple Linear Regression Analysis was employed to test the relationship between the WebQual 4.0 variables and User Satisfaction. The findings are expected to provide innovation for the development of the AIS at PGRI Palembang University.